The Trace element geochemistry and geotectonic settings of the charnockitic and associated rocks around ikare, southwestern Nigeria - Victor Alaba Oyeshomo , Anthony; Altenberger , Uwe; Bolarinwa , Anthony (International Journal of Advanced Geosciences, 2024)
The trace element concentrations of charnockites and associated rocks around Ikare were investigated in this study. Previous works on the genesis and tectonic settings of these rocks around Ikare were inconclusive due to lack of trace element data. Hence, this study was designed to determine the trace element compositions and use them to interpret their tectonic setting. Forty (40) representative rock samples were subjected to geochemical analyses using inductively coupled- plasma mass spectrometer. Results showed that most rocks are enriched in Ba, Sr, Zr but depleted in Rb suggesting their improverishment in the source rock. K/Rb ratios ranged from 153ppm to 374ppm for all rocks, while Ba/Sr ratios are high indicating that they are not mantle derived but through internal differentiation of pre-existing TTGs intra-crustal melting. On the Sr/Y discrimination diagram, the rocks plot in the post-Archean field. On the Y versus Nb and Rb versus Y+Nb, the rocks indicated magmatic origin in pre-to syn-collisional orogenic tectonic setting.